Probe pin, thermocouple and electronic tube heater
A tungsten wire alloyed with rhenium and controlled surface composition addresses breakage and irregularities in small-diameter wires, enhancing yield and precision through controlled processing techniques.
Patent Information
- Application Number
- JP2024159006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-17
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-02-10
AI Technical Summary
Existing methods for producing small-diameter tungsten wires, such as those used in probe pins and thermocouples, suffer from high breakage rates and surface irregularities due to factors like die marks and uneven surface composition, leading to reduced yield and increased processing costs.
A tungsten wire alloyed with rhenium and containing a controlled mixture of W, C, and O on its surface, with specific ratios and uniform thickness distribution, is processed through a series of controlled rolling, recrystallization, and electrolytic polishing steps to enhance strength and uniformity.
The solution significantly reduces breakage and surface irregularities during wire drawing, improving yield and reducing defects, making it suitable for high-precision applications like probe pins and thermocouples.
Smart Images

Figure 2025003993000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiments described below relate to a tungsten wire, a tungsten wire processing method using the same, and an electrolytic wire. [Background technology]
[0002] Various tungsten (W) wires have been used as cathode heaters for TV electron guns, filament materials for lighting in automobile lamps and home appliances, high-temperature structural components, contact materials, and discharge electrodes. Among these, tungsten alloy (ReW) wires containing a certain amount of rhenium (Re) have excellent high-temperature strength and ductility after recrystallization, and are widely used as heaters for electron tubes and filament materials for vibration-resistant light bulbs. In addition, they have excellent electrical resistance characteristics and abrasion resistance, and are used as components of high-temperature thermocouples and, in particular, probe pins for probe cards used to test the electrical characteristics of semiconductor integrated circuit (LSI) wafers. This test is performed by directly applying a probe pin, the tip of which has been chemically or mechanically processed into a shape favorable for contact, to the terminal of the test object.
[0003] With the progress of semiconductor integration and miniaturization technology, there is a continuing demand for probe cards with finer pin pitch and smaller diameter, and currently ReW pins with a wire diameter of 0.02mm to 0.04mm are also being used. A smaller wire diameter for the probe pin allows for a larger number of pins per unit area, which is advantageous for testing highly integrated LSIs.
[0004] In the case of such small diameter W wire (thin wire), first, the sintered body is subjected to rolling and wire drawing (wire drawing) processing (primary processing) to produce a wire of a certain diameter range (0.3mm to 1.5mm). Then, the appropriate amount of wire is subjected to necessary processes such as wire drawing and heat treatment to produce a specified tungsten wire (wire diameter). In this thinning process, breaks during wire drawing and fine linear irregularities that appear in the wire drawing direction on the material surface (die marks: described in JIS H0201 718) are likely to occur. Breaks during wire drawing of thin wires significantly reduce the yield, especially in multi-stage wire drawing machines that process with multiple dies. In addition, repairs and restarting after wire breakage increase the number of man-hours. If die marks cannot be removed by subsequent surface polishing and probe pin processing, they become defects that worsen the yield and processing costs.
[0005] Conventional countermeasures against wire breakage include those that improve workability by controlling the number of recrystallizations through heat treatment in the middle of the process. For example, when the cross-sectional area reduction rate (area reduction rate) of the molded product from the sintered body exceeds 75% and reaches 90% or less, a final recrystallization process is carried out to reduce the number of recrystallized grains in the center and surface layer of the molded product to 500 grains / mm. 2 ~800 pieces / mm 2 There is a ReW wire that adjusts the thickness to 100 nm (see Patent Document 1). There are also wires that have improved workability by controlling the Re segregation phase (σ phase) in the W matrix. For example, if the σ phase is unevenly distributed, wire breaks are likely to occur starting from the σ phase during wire drawing, so there is a ReW wire in which the maximum grain size of the σ phase is set to 10 μm or less (see Patent Document 2). Furthermore, in secondary processing such as coil processing, if a lubricant containing graphite (C) remains in the recesses on the material surface, this C component may contaminate and embrittle the W at high temperatures during processing. For this reason, some wires prevent embrittlement by controlling the surface roughness. For example, there is a ReW wire that is drawn to a wire diameter of 0.175 mm and then electrolyzed to adjust the average interval and maximum height of the recesses on the material surface to a specified range (see Patent Document 3).
[0006] Regarding die marks, a common method is to remove them by a chemical polishing (electrolysis) process after wire drawing to a specified size. For example, there is a manufacturing method for W electrodes in which the center line average roughness and ten-point average roughness are specified and electrolytic processing is performed to those values (see Patent Document 4). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent No. 2637255 [Patent Document 2] Japanese Patent No. 4256126 [Patent Document 3] Japanese Patent No. 3803675 [Patent Document 4] Japanese Patent Publication No. 2000-100377 Summary of the Invention [Problem to be solved by the invention]
[0008] The method of controlling the number of crystals by heat treatment in the middle process described in Patent Document 1 requires a certain reduction in area from the sintered body to the recrystallization process. In addition, this effect is related to processing to the above-mentioned material size, which is a finished diameter of 1.0 mm. When considering application to thin wires, the cross-sectional area of the sintered body needs to be very small, which greatly reduces productivity. In addition, the small recrystallization process size is likely to reduce the strength at the finished size. For example, probe pins are difficult to use because they are required to be strong enough not to deform when they come into contact with the terminal of the test object. The method described in Patent Document 2 is very effective for preventing breaks originating from the σ phase. However, the segregation of the σ phase is controlled in the process up to the production of the sintered body, and the subsequent processes are the same as in the past. Therefore, breaks due to other factors such as die marks are not suppressed. Patent Document 3 describes a method for preventing embrittlement due to a reaction between W and C by giving a fine wire good surface properties, and easily evaporating the C remaining on the surface by high-temperature heating during secondary processing such as coiling. In the fine wire processing described in Patent Document 3, a C-based lubricant with excellent heat resistance is generally used. The measure of evaporating C deteriorates lubricity and creates a risk of seizure between the wire and the die.
[0009] Patent Document 4 describes a method for removing and managing die marks that have occurred, but does not mention how to suppress die marks.
[0010] The problem to be solved by the present invention is to provide a W wire for wire drawing which improves breakage during drawing and surface unevenness. [Means for solving the problem]
[0011] In order to solve the above problems, the tungsten (W) wire according to the embodiment is a W wire made of a W alloy containing rhenium (Re), and has a mixture on at least a part of the surface, the mixture containing W, C, and O as constituent elements, and when the radial cross-sectional thickness of the mixture is A mm and the diameter of the W wire is B mm, the average value of the ratio A / B of A to B in the same cross section is 0.3% or more and 0.8% or less. Also provided are probe pins, thermocouples, and electron tube heaters using the above tungsten wire. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram showing an example of a tungsten wire for wire drawing according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram of a radial cross section of the tungsten wire (cross section XX in FIG. 1). [Diagram 3] FIG. 3 is a schematic diagram of the mixture at an arbitrary point A in a radial cross section. [Figure 4-1] FIG. 4-1 is a graph showing the change in oxygen content of the mixture (EPMA line analysis) in a radial cross section in Comparative Example 3. [Figure 4-2] FIG. 4-2 is a graph showing the change in oxygen content of the mixture in a radial cross section in Example 2 (EPMA line analysis). [Diagram 5] FIG. 5 is a cross-sectional schematic diagram showing a deformation model of a wire during drawing and the stresses at the center and surface. [Figure 6-1] FIG. 6-1 is a schematic diagram of Comparative Example 3 for illustrating the difference in the shape of the mixture layer between Comparative Example 3 and Example 2 in radial cross section. [Figure 6-2] FIG. 6-2 is a schematic diagram of Example 2 for illustrating the difference in the shape of the mixture layer between Comparative Example 3 and Example 2 in radial cross section. [Figure 7-1] FIG. 7-1 is a cross-sectional view showing the radial cross-sectional shape (overall view) of a wire body before electrolytic polishing. [Figure 7-2] FIG. 7-2 is a cross-sectional view showing the radial cross-sectional shape (overall view) of the wire body after electrolytic polishing. Embodiment
[0013] Hereinafter, the tungsten wire for wire drawing of the embodiment will be described with reference to the drawings. Hereinafter, the tungsten wire for wire drawing may be referred to as the W wire for wire drawing. Note that the drawings are schematic, and for example, the dimensional ratio of each part is not limited to the drawings.
[0014] Figure 1 shows an example of a W wire sample taken from a W wire for wire drawing. The sample length should be, for example, 100mm to 150mm long enough to allow multiple cross-sectional observations after embedding in resin. The sampling position is arbitrary, but in order to ensure a high yield rate in the subsequent processes, it is best to sample from a position other than the front and rear ends. The front and rear ends have parts where the conditions become unstable due to the start and stop of the wire drawing device, so these parts are not included in the sampling. The length of the unstable part varies depending on the layout and size of the device. The diameter of the sample taken is measured in the XY direction using a micrometer. Measurements are performed at three locations, and the average of the six data obtained is taken as the diameter B (mm) of each sample.
[0015] FIG. 2 shows the XX cross section (cross section perpendicular to the wire drawing direction: radial cross section) of FIG. 1. As shown in the figure, a straight line is drawn through the center to divide the sample into eight equal parts, and the intersections with the outer periphery are designated A1 to A8. The mixture is observed at any eight equally spaced points on the periphery. FIG. 3 shows a schematic diagram of the mixture at any one of the points. For example, the sample can be embedded in resin and polished to obtain a clearer observation image, but the mixture may peel off during this process. Such parts are excluded from the measurement points. Using an SEM image observed at 10,000 times magnification, the thickest part of the mixture (A max ) and the thinnest part (A min ) and the average value is the thickness of the mixture. In the same manner, the thickness is calculated for each of the eight points (A1 to A8) on the same cross section. The thickness at any one of these points is designated A (mm). Using the diameter B of the observed sample, the ratio A / B (%) of A to B is calculated. For the same cross section, the number of data points for A / B is 8. Depending on the number of samples observed (n), the number of data points for A / B is "8 x n".
[0016] The average value of A / B of the tungsten wire of the embodiment is 0.3% or more and 0.8% or less (0.003 or more and 0.008 or less). More preferably, it is 0.3% or more and 0.6% or less (0.003 or more and 0.006 or less). If the average value of A / B is smaller than 0.3%, breakage occurs during wire drawing, and if the ratio of A / B is larger than 0.8%, the rate of die marks occurring increases. If the average value of A / B is within the range of 0.3% or more and 0.8% or less, breakage during wire drawing and the occurrence of die marks can be suppressed.
[0017] FIG. 4 (FIG. 4-1 and FIG. 4-2) shows, as an example, the results of an analysis of the amount of O (oxygen) in the mixture in a radial cross section with a diameter of 0.80 mm. FIG. 4-1 shows the results of the measurement of a portion of Comparative Example 3, and FIG. 4-2 shows the results of the measurement of a portion of Example 2. The analysis was performed using an EPMA (electron probe microanalyzer: JXA-8100 manufactured by JEOL Ltd.), with an accelerating voltage of 15 kV and a sample current of 5.0×10 -8A, Beam diameter: Spot (~Φ1μm), Analysis time: 500ms / point, Scan mode: Stage scan, Analysis distance: 29.7μm (151 points). The vertical axis is the count number, and the horizontal axis is the observation direction distance. Hereinafter, Comparative Example 3 may be referred to as the conventional W line. The A / B ratio of the observed area is 1.4% (0.014) for the conventional W wire and 0.7% (0.007) for Example 2. The O in the mixture of the conventional W wire fluctuates in the cross-sectional direction (length L of the mixture), whereas the O in Example 2 is stable. The O in the mixture exists as a compound (oxide) with W. The oxide composition of W includes WO3, W 20 O 58 , W 18 O 49 , WO2, and W3O, and their physical properties (strength, adhesion) are different. In conventional W wire, the O in the cross section of the mixture fluctuates, indicating that oxides of different compositions exist within the cross section. This causes non-uniform deformation during wire drawing, which can lead to cracks and falling off of the oxide film. The fallen parts are likely to become die marks.
[0018] Figure 5 shows a deformation model of the wire during drawing, and the stresses at the center and surface. Shear forces are generated in the surface layer of the wire due to contact with the die during drawing. The outer periphery 1 also undergoes plastic deformation due to the shear forces. As a result, the material does not stretch uniformly in the radial cross section, but is more advanced towards the center 2. When the mixture on the surface is thick, the amount of shear deformation in the mixture layer is greater than when it is thin. For this reason, the shear force acting between the W and the mixture is greater when the layer is thick. This causes partial shedding of the mixture. The presence of oxides with different compositions in the mixture as mentioned above makes shedding more likely to occur.
[0019] If the average value of A / B is less than 0.3% (0.003), there is a high risk of W and C reacting directly, causing embrittlement. In addition, there is a possibility that lubricity cannot be sufficiently secured.
[0020] Next, for A / B of the same cross section (8 data points), the average value (Ave), standard deviation (Sd), and coefficient of variation (CV) calculated by Sd / Ave are calculated. CV indicates the ratio of the magnitude of data variation to the average, and can be used to compare variations regardless of whether the layer thickness is thin or thick.
[0021] The CV of the tungsten wire in the same cross section of the embodiment is preferably 0.30 or less. More preferably, it is 0.20 or less. If the CV is greater than 0.30, there is a high possibility of breakage or die marks occurring during wire drawing. If the thickness of the mixture varies greatly, there is a possibility that A / B may be large or small in some parts. In such parts, there is a risk of defects such as the above-mentioned dropping or cracking of the mixture, and C embrittlement of the W wire.
[0022] Figure 6 (Figure 6-1 and Figure 6-2) shows, as an example, a schematic diagram of the difference in the shape of the mixture in a radial cross section with a diameter of 0.8 mm. When an actual sample was observed using an SEM at a magnification of 5000 times for a cross section with a circumferential length of 60 μm, the conventional wire had a difference in thickness (A ma x‐A min ) was 6 μm, while in Example 2 it was 1 μm, a large difference. Furthermore, the CV of this cross section was found to be 0.5 for the conventional wire and 0.1 for Example 2. When the CV is large, it is highly likely that there is a large difference (variation) in thickness not only depending on the position on the periphery, but also in the same location. A mixture layer of this type does not have a uniform processing force during wire drawing, making it prone to cracking and falling off.
[0023] The cross-section from which the A / B data was obtained is subjected to energy dispersive X-ray analysis (EDS: accelerating voltage 15 kV, magnification 10,000 times, measurement range 30 μm × 30 μm) using a Phenom ProX desktop scanning electron microscope. max and A minThen, the center of the mixture in the thickness direction is measured and the average value is calculated. Measurements are performed at any five of the eight locations (A1 to A8) on the cross section, and the ratio of each location (Owt% / Wwt%) is calculated from the obtained data values for W (wt%) and O (wt%). Note that W (wt%) is the mass% of tungsten, and O (wt%) is the mass% of oxygen.
[0024] In the embodiment, the W wire preferably has an average ratio of O (wt%) to W (wt%) (Owt% / Wwt%) of 0.10 or less at the center of the mixture in the thickness direction. If it exceeds 0.10, the generation of WO3 among the W oxides may progress. Since WO3 has very brittle properties, the mixture is likely to fall off. The lower limit is not particularly limited, but is preferably 0.05 or more. If it is below 0.05, the generation of W oxides is insufficient, and the reaction between C in the C layer and W is likely to occur.
[0025] The amount of Re contained in the W wire of the embodiment is preferably 1 wt% or more and 30 wt% or less, and more preferably 2 wt% or more and 28 wt% or less. If the Re content is less than 1 wt%, the strength decreases, and when used in a probe pin, for example, the amount of deformation increases with frequency of use, causing contact failure and reducing the inspection accuracy of semiconductors. If the Re content is greater than about 28 wt%, the solid solubility limit with W is exceeded, and the σ phase is likely to be unevenly distributed. This phase may become the starting point of fracture during wire drawing, significantly reducing the processing yield. By setting the Re content to 1 wt% or more and 30 wt% or less, or 2 wt% or more and 28 wt% or less, for example, an electrolytic wire for a probe pin made of the material of this embodiment can be manufactured with a high yield while maintaining mechanical properties (strength and abrasion resistance).
[0026] The W wire of the embodiment may contain 30wtppm to 90wtppm of K as a dopant. By containing K, the tensile strength and creep strength at high temperatures are improved by the doping effect. If the K content is less than 30wtppm, the doping effect is insufficient. If it exceeds 90wtppm, the processability may decrease, and the yield may be significantly reduced. By containing 30wtppm to 90wtppm of K as a dopant, for example, thin wires for thermocouples and electron tube heaters made of the material of this embodiment can be manufactured with good yield while ensuring high-temperature properties (prevention of breakage and deformation when used at high temperatures).
[0027] According to this embodiment, a tungsten wire for wire drawing can be realized that suppresses breakage and surface irregularities during thin wire processing, greatly contributing to improved yield, and can be applied to electrolytic wire applications for probe pins. It can also be applied to high-temperature thermocouple applications.
[0028] Next, a method for producing the W wire for wire drawing according to the present embodiment will be described. The method for producing the W wire for wire drawing is not particularly limited, but the following method can be given as an example.
[0029] W powder and Re powder are mixed so that the Re content is 1 wt% or more, for example, 3 wt% or more and 30 wt% or less. Although the mixing method is not particularly limited, a method of mixing the powder in a slurry state using water or an alcohol-based solution is particularly preferred because it produces a powder with good dispersibility. The Re powder to be mixed is preferably one having a maximum particle size of less than 100 μm. Also, it is preferably one having an average particle size of less than 20 μm. The W powder is pure W powder excluding unavoidable impurities, or doped W powder containing a K amount considering the yield up to the wire rod. The W powder is preferably one having an average particle size of less than 30 μm. If the maximum particle size or average particle size of the Re powder is above the above, coarse σ phase is easily generated. Also, if the average particle size of the W powder is above the above, the moldability decreases during the press molding in the subsequent process, and breaks, chips, cracks, etc. are easily generated in the molded body.
[0030] For example, when manufacturing a W-Re mixed powder with a Re content of more than 18wt%, first, a ReW alloy with a Re content of 18wt% or less is produced by powder metallurgy, melting, etc., and then finely pulverized by a conventional method. There is also a method of mixing the insufficient amount of Re to the desired composition. Hereafter, tungsten wire containing Re may be referred to as ReW wire.
[0031] Next, the mixed powder is put into a predetermined mold and press molded. The pressing pressure at this time is preferably 100 MPa or more. The molded body may be pre-sintered at 1200°C to 1400°C in a hydrogen furnace to facilitate handling. The obtained molded body is sintered in a hydrogen atmosphere, an inert gas atmosphere such as argon, or in a vacuum. The sintering temperature is preferably 2125°C or more. If the temperature is less than 2125°C, densification by sintering does not progress sufficiently. The upper limit of the sintering temperature is 3400°C (lower than the melting point of W, 3422°C). The relative density after sintering (relative density to true density (%) = [sintered body density / true density] × 100%) is preferably 90% or more. By making the relative density of the sintered body 90% or more, it is possible to reduce the occurrence of cracks, chips, breaks, etc. in the subsequent rolling and punching process (SW).
[0032] The molding and sintering may be performed simultaneously by hot pressing in a hydrogen atmosphere, an inert gas atmosphere such as argon, or in a vacuum. The pressing pressure is preferably 100 MPa or more, and the heating temperature is preferably 1700°C to 2825°C. This hot pressing method can obtain a dense sintered body even at a relatively low temperature.
[0033] The sintered body obtained in the sintering step is subjected to a first rolling and punching process. The first rolling and punching process is preferably carried out at a heating temperature of 1300° C. to 1600° C. The reduction rate of the cross-sectional area (area reduction rate) in one heat treatment (one heat) is preferably 5% to 15%.
[0034] Instead of the first rolling and punching process, rolling may be performed. The rolling is preferably performed at a heating temperature of 1200°C to 1600°C. The area reduction rate in one heat is preferably 40% to 75%. As the rolling mill, a two-way roller rolling mill, a four-way roller rolling mill, a die roll rolling mill, or the like can be used. The rolling process can significantly increase the manufacturing efficiency. The first rolling and punching process may be combined.
[0035] The second rolling process is carried out on the sintered body (ReW bar material) that has been subjected to the first rolling process, rolling process, or a combination of these processes. The second rolling process is preferably carried out at a heating temperature of 1200°C to 1500°C. The reduction in area in one heat is preferably about 5% to 20%.
[0036] The ReW bar that has been through the second rolling step is then subjected to a recrystallization treatment. The recrystallization treatment can be carried out, for example, using a high-frequency heating device in a hydrogen atmosphere, an inert gas atmosphere such as argon, or in a vacuum at a treatment temperature in the range of 1800°C to 2600°C.
[0037] The ReW bar material that has completed the recrystallization treatment is subjected to a third rolling process. The third rolling process is preferably performed at a heating temperature of 1200°C to 1500°C. The area reduction rate in one heat is preferably about 10% to 30%. The third rolling process is performed until the ReW bar has a diameter that can be drawn (preferably a diameter of 2 mm to 4 mm).
[0038] The ReW bar material that has completed the third rolling process is subjected to the first wire drawing process, which repeats the process of applying a lubricant to the surface, drying the lubricant, heating to a processable temperature, and drawing using a drawing die to enable smooth wire drawing, until the diameter is 0.7 mm to 1.2 mm. It is preferable to use a C-based lubricant with excellent heat resistance as the lubricant. The processing temperature is preferably 800°C to 1100°C. The processable temperature varies depending on the diameter, and is higher as the diameter increases. If the temperature is lower than the processable temperature, cracks and breakage occur frequently. If the temperature is higher than the processable temperature, seizure occurs between the wire and the die, the deformation resistance of the wire decreases, and the drawing force causes the diameter to fluctuate (thinning) after drawing. The reduction in area is preferably 15% to 35%. If it is less than 15%, internal and external differences in the structure and residual stress occur during processing, which cause cracks. If it is more than 35%, the drawing force becomes excessive, causing the diameter after drawing to fluctuate significantly and break. The wire drawing speed is determined by the balance between the capacity of the heating device, the distance from the device to the die, and the reduction in area.
[0039] The composition of the mixture formed on the surface, especially the W oxide, varies depending on the processing conditions (heating temperature, atmosphere, etc.). Repeated heating makes the processing conditions more likely to fluctuate. In addition, the optimum processing temperature changes with changes in diameter. In particular, when the diameter is large, the heating temperature needs to be high, and the conditions are more likely to fluctuate. For this reason, there is a high possibility that W oxides with different compositions will be generated as the thickness increases. Therefore, wires drawn to a diameter of 0.7 mm to 1.2 mm are polished to remove the mixture formed on the surface during previous processing and the unevenness of the wire surface.
[0040] The polishing process may be, for example, electrochemical polishing (electrolytic polishing) in a sodium hydroxide solution with a concentration of 7 wt% to 15 wt%. The reduction in area in the polishing process is preferably 10 to 25%. If it is less than 10%, it may be impossible to remove the unevenness of the material surface generated in the rolling process and the first wire drawing process and the mixture adhering thereto. If it exceeds 25%, the material yield will deteriorate. In the case of electrolytic polishing, the processing speed is preferably 0.5 m / min to 2.0 m / min. If it is slower than 0.5 m / min, the processing man-hours will increase significantly. If it exceeds 2.0 m / min, the amount of electrolysis per unit time will increase, resulting in rapid electrolysis, and the correction of the wire cross-sectional shape may be insufficient. Alternatively, the device must be very large. Figure 7 (Figures 7-1 and 7-2) shows the results of observing the radial cross-sectional shape of the ReW wire body before and after electrolytic polishing in schematic diagrams. The unevenness of the wire surface has disappeared by electrolytic polishing.
[0041] After polishing, the wire is heated in an atmospheric furnace to form a dense and homogeneous oxide layer on the surface. The heating temperature is preferably 700°C to 1100°C. If the heating temperature is lower than 700°C, oxides are difficult to form. If the heating temperature is higher than 1100°C, the oxide composition will vary. The processing speed is preferably 5m / min to 20m / min. If the processing speed is lower than 5m / min, the processing man-hours will increase significantly. If the processing speed is higher than 20m / min, the amount of heat required to raise the temperature will need to be increased, and the oxide layer will tend to become non-homogeneous. Alternatively, the equipment will need to be very large.
[0042] To form and adhere the C layer on the oxide layer, a process of applying a lubricant to the surface, a process of drying the lubricant and heating to a workable temperature, and a process of drawing using a drawing die are performed. By adhering the C layer, changes and peeling of the oxide layer in the subsequent process are prevented. The reduction in area is preferably 10% to 30%, more preferably 15% to 25%. If it is less than 10%, there is a risk that the oxide layer and the C layer will not adhere sufficiently. If it is more than 30%, the drawing force becomes too large, and there is a risk that peeling of the layer occurs on the die entry side.
[0043] After this, the second wiredrawing process is performed. The heating temperature is preferably 1000°C or less. If the temperature exceeds 1000°C, the C in the adhesive C layer reacts with O in the air to become CO2 and is released, the C layer becomes sparse, and the composition of the oxide layer underneath may change. The area reduction rate of the second wiredrawing process is preferably 15% to 35%, similar to the first wiredrawing process. The second wiredrawing process produces a W wire for wiredrawing with a diameter of 0.3 mm to 1.0 mm.
[0044] After this, the appropriate amount of W wire for wire drawing is subjected to necessary processes such as wire drawing and heat treatment to produce a W wire with the required characteristics (strength, hardness, etc.) at the specified wire diameter. This is then electrolytically polished to produce an electrolytic wire. (Example)
[0045] By the above-mentioned powder mixing, molding, and sintering methods, sintered bodies were manufactured with the compositions shown in Table 1. In Examples 1 to 6, the first rolling and punching process, rolling process, second rolling and punching process, recrystallization treatment, third rolling and punching process, first wiredrawing process, electrolytic polishing, heat treatment for forming an oxide layer, wiredrawing process for adhering the C layer, and second wiredrawing process were performed to obtain the diameters shown in Table 1.
[0046] In Example 7, the reduction rate was reduced to 8% in the electrolytic polishing process after the first wiredrawing. In Comparative Example 1, the heat treatment temperature for forming an oxide layer after electrolytic polishing was reduced to 680°C to 700°C, and the mixture layer was thinned. In Comparative Example 2, the heating temperature was increased to 1150°C in the second wiredrawing, and the mixture layer was thickened. In Comparative Examples 3 to 5, the conventional processing step was carried out in which the second wiredrawing was carried out directly after the first wiredrawing. Each wire was processed to the diameter shown in Table 1. The analysis of Re and K was carried out by inductively coupled plasma-optical emission spectrometry (ICP-OES), which is suitable for evaluating constituent elements, rather than by inductively coupled plasma-mass spectrometry (ICP-MS), which is suitable for evaluating trace impurities. The lower detection limit for K is 5 wtppm, and if the analytical value falls below 5 wtppm without addition, it is recorded as "-".
[0047] [Table 1]
[0048] Sampling was done from the obtained wire, and A / B, CV, and Owt% / Wwt% were evaluated by the above-mentioned method. The mixture contained W, C, and O as constituent elements. 1 kg of this wire was used and drawn to a diameter of 0.08 mm. The rate of break failure during drawing and the rate of appearance failure after completion were investigated. The breakage failure rate was calculated by counting the weight of a wire after breakage, which was ≦0.05 kg during drawing, as a defective weight and dividing the total defective weight by the input weight (1 kg). The appearance defect rate was determined by cutting 100m of each end of the wire after drawing to a length of 50mm, boiling it in caustic soda, and removing any impurities. The wire was then observed under a microscope at 30x magnification, and if there were any visible scratches or irregularities on the surface, 50mm was counted as a die mark defect. The length of the defect was calculated and calculated as the defective length / evaluation length (200m). The results are shown in Table 2.
[0049] [Table 2]
[0050] As can be seen from the table, the W wire for wire drawing according to the embodiment had a reduced rate of wire drawing breakage and a reduced rate of appearance defects. On the other hand, the comparative example had a high rate of wire drawing breakage and a low rate of appearance defects.
[0051] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. Modifications of these embodiments are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. The invention as originally claimed in the present application is set forth below. [1] A tungsten wire made of a tungsten alloy containing rhenium, having a mixture on at least a portion of a surface thereof, the mixture containing W, C, and O as constituent elements, and wherein, when a radial cross-sectional thickness of the mixture is A mm and a diameter of the tungsten wire is B mm, an average ratio A / B of A to B is 0.3% or more and 0.8% or less. [2] The tungsten wire according to [1], wherein the coefficient of variation of A / B in the same cross section is 0.30 or less. [3] The tungsten wire according to any one of [1] to [2], wherein in the mixture, the average ratio of O (wt%) to W (wt%) (Owt% / Wwt%) at the center in the thickness direction of the radial cross section is 0.05 or more and 0.10 or less. [4] The tungsten wire according to any one of [1] to [3], wherein the rhenium content is 1 wt% or more and 30 wt% or less. [5] The tungsten wire according to any one of [1] to [3], wherein the rhenium content is 2 wt% or more and 28 wt% or less. [6] The tungsten wire according to any one of [1] to [5], wherein the tungsten alloy has a potassium (K) content of 30 wtppm or more and 90 wtppm or less. [7] The tungsten wire according to any one of [1] to [6], wherein the diameter of the tungsten wire is 0.3 mm or more and 1.0 mm or less. [8] A tungsten wire processing method, comprising the steps of: drawing a tungsten wire according to any one of [1] to [7]. [9] An electrolytic wire using a tungsten wire that has been drawn using the tungsten wire processing method described in [8].
[10] A tungsten wire according to any one of [1] to [7], which is for wire drawing. [Explanation of symbols]
[0052] XX: Cut surface perpendicular to the wire drawing axis (radial direction) Y...Mixture Z…ReW wire body A1 to A8: Points dividing the circumference into eight equal parts on the radial cut surface A max …Maximum thickness of the mixture within the observation field A min …Minimum thickness of mixture within the observation field 1...Outer periphery 2…Center
Claims
1. A probe pin using a tungsten wire, A probe pin, wherein the tungsten wire is made of a tungsten alloy containing rhenium and has a mixture on at least a portion of its surface, the mixture containing W, C, and O as constituent elements, and when a radial cross-sectional thickness of the mixture is A mm and a diameter of the tungsten wire is B mm, an average value of a ratio A / B of A to B in the same cross section is 0.3% or more and 0.8% or less.
2. The probe pin according to claim 1 , wherein the coefficient of variation of the A / B in the same cross section is 0.30 or less.
3. 3. The probe pin according to claim 1, wherein in the mixture, an average value of a ratio of O (wt%) to W (wt%) (O wt% / W wt%) at a thickness-direction center portion of a radial cross section is 0.05 or more and 0.10 or less.
4. 3. The probe pin according to claim 1, wherein the content of said rhenium is 1 wt % or more and 30 wt % or less.
5. 3. The probe pin according to claim 1, wherein the content of said rhenium is 2 wt % or more and 28 wt % or less.
6. 3. The probe pin according to claim 1, wherein the diameter of the tungsten wire is not less than 0.3 mm and not more than 1.0 mm.
7. A thermocouple using a tungsten wire, The tungsten wire is made of a tungsten alloy containing rhenium and has a mixture on at least a portion of a surface thereof, the mixture containing W, C, and O as constituent elements, and when a radial cross-sectional thickness of the mixture is A mm and a diameter of the tungsten wire is B mm, an average value of a ratio A / B of A to B in the same cross section is 0.3% or more and 0.8% or less.
8. 8. The thermocouple according to claim 7, wherein the coefficient of variation of A / B in the same cross section is 0.30 or less.
9. 9. The thermocouple according to claim 7, wherein in the mixture, an average value of a ratio of O (wt%) to W (wt%) (O wt% / W wt%) at a central portion in a thickness direction of a radial cross section is 0.05 or more and 0.10 or less.
10. The thermocouple according to any one of claims 7 to 8, wherein the tungsten alloy has a potassium (K) content of 30 wtppm or more and 90 wtppm or less.
11. 9. The thermocouple according to claim 7, wherein the tungsten wire has a diameter of 0.3 mm or more and 1.0 mm or less.
12. An electron tube heater using a tungsten wire, An electron tube heater, wherein the tungsten wire is made of a tungsten alloy containing rhenium and has a mixture on at least a portion of its surface, the mixture containing W, C, and O as constituent elements, and when a radial cross-sectional thickness of the mixture is A mm and a diameter of the tungsten wire is B mm, an average value of a ratio A / B of A to B in the same cross section is 0.3% or more and 0.8% or less.
13. 13. The electron tube heater according to claim 12, wherein the coefficient of variation of A / B in the same cross section is 0.30 or less.
14. An electron tube heater as described in any one of claims 12 to 13, wherein in the mixture, the average ratio of O (wt%) to W (wt%) (O wt% / W wt%) at the thickness-wise center of the radial cross section is 0.05 or more and 0.10 or less.
15. 14. The electron tube heater according to claim 12, wherein the tungsten alloy has a potassium (K) content of 30 wtppm or more and 90 wtppm or less.
16. 14. The electron tube heater according to claim 12, wherein the diameter of the tungsten wire is 0.3 mm or more and 1.0 mm or less.
Citation Information
Patent Citations
W3Re-W25Re thermocouple material and preparation method of thermocouple
CN102586663A
Device for heating sample to high temperature
JP1983104150A
Rhenium-tungsten wire, probe pin and inspection instrument provided with the probe pin
JP2002356732A
Saw wire and cutting device
JP2018187741A
Metal wire and saw wire
JP2019131841A